Elaboration of a kinetic model in order to predict the molecular and isotopic composition of natural gas generated during the thermal cracking of hydrocarbons - Fusetti, Luc (Curtin University, 2009)
The scope of the present study was to validate an approach that could be used to elaborate a model that would predict the δ[superscript]13C of the gases generated during thermal cracking of oil. The attention was focused on C[subscript]14- methylaromatics and alkylaromatics but the entire methodology was demonstrated on one component i.e. 1,2,4-trimethylbenzene.Pyrolysis experiments at temperatures of 395, 425, 450, and 475 °C and at a pressure of 100 bar were performed in order to study the whole range of conversions. All pyrolysis fractions were recovered and quantified. All identified products were also quantified individually. A free-radical mechanism until 70% conversion of 1,2,4-trimethylbenzene was achieved. This mechanism was then used to characterize some CH[subscript]4 generation pathways at 425 and 200 °C. In both cases the identified pathways included: (i) demethylation of 1,2,4- trimethylbenzene into xylenes (and to a lesser extent demethylation of xylenes into toluene), (ii) dimerizarion of monoaromatics, (iii) intramolecular ring closure reaction of dimers into triaromatics.In a second step, the free-radical mechanism was used to constrain the chemistry of a simpler lumped kinetic model predicting CH[subscript]4 generation under laboratory and geological conditions for the whole range of conversions. The resulting scheme was composed of four pathways P[subscript]i for methane generation: Reactant --> Dimers (P[subscript]a), Reactant --> Xylenes (P[subscript]b), Dimers --> {Prechar + Char} (P[subscript]c), and Xylenes --> Dimers + Toluene (P[subscript]d). Optimization yielded activation energies in the range of 50-60 kcal/mol, and frequency factors in the neighbourhood of 10[superscript]12 s[superscript]-1. Simulations revealed that P[subscript]b and P[subscript]c led to the greatest amounts of CH[subscript]4 below 5% conversion, followed by P[subscript]a. Above 5% conversion, CH[subscript]4 generated via P[subscript]c became dominant but P[subscript]a and P[subscript]b were also found to be of importance. Contribution of P[subscript]d was found to be negligible, except for when 100% conversion was almost reached. Simulations under geological heating rates revealed that significant amounts of CH[subscript]4 were generated by methylated monoaromatics in deeply buried reservoirs and that methylated monoaromatics thus had a higher thermal stability than their polyaromatic counterparts but lower than the saturated hydrocarbons.CH[subscript]4 yield was also modelled using a unique stoichiometric equation (CH[subscript]4max = 7.6 wt% per methyl group) associated with Ea = 58.5 kcal/mol and A = 10[superscript]11.96 s[superscript]-1, showing relative similarities to other reported values for methylated polyaromatics. In the final stage, P[subscript]a, P[subscript]b, and P[subscript]c were selected as relevant contributions to δ[superscript]13C[subscript]CH4 until 100% conversion. Kinetics for the generation of [superscript]12CH[subscript]4 and [superscript]13CH[subscript]4 were then expressed separately and implemented into the lumped model. Optimization yielded a ratio of frequency factors Ω = 1.028, variations of activation energy ΔE[subscript]i in the range of 36-79 cal/mol (kinetic effect); and a δ[superscript]13C[subscript]p of CH[subscript]4 precursor groups equal to -32.7‰ (precursor effect). Simulations performed under geological heating rates illustrated the greater isotopic fractionation of CH[subscript]4 generated under geological conditions compared with laboratory conditions. The comparison at high maturity with δ[superscript]13C[subscript]CH4 during thermal cracking of 1-methylpyrene and mature kerogen under the same simulation conditions emphasized the need to determine the magnitude of the precursor effect for natural compounds.